Selective Deletion of the Brain-Specific Isoform of Renin Causes Neurogenic Hypertension. Issue 6 (December 2016) - Shinohara, Keisuke; Liu, Xuebo; Morgan, Donald A.; Davis, Deborah R.; Sequeira-Lopez, Maria Luisa S.; Cassell, Martin D.; Grobe, Justin L.; Rahmouni, Kamal; Sigmund, Curt D.
Abstract : The renin–angiotensin system (RAS) in the brain is a critical determinant of blood pressure, but the mechanisms regulating RAS activity in the brain remain unclear. Expression of brain renin (renin-b) occurs from an alternative promoter-first exon. The predicted translation product is a nonsecreted enzymatically active renin whose function is unknown. We generated a unique mouse model by selectively ablating the brain-specific isoform of renin (renin-b) while preserving the expression and function of the classical isoform expressed in the kidney (renin-a). Preservation of renal renin was confirmed by measurements of renin gene expression and immunohistochemistry. Surprisingly, renin-b–deficient mice exhibited hypertension, increased sympathetic nerve activity to the kidney and heart, and impaired baroreflex sensitivity. Whereas these mice displayed decreased circulating RAS activity, there was a paradoxical increase in brain RAS activity. Physiologically, renin-b–deficient mice exhibited an exaggerated depressor response to intracerebroventricular administration of losartan, captopril, or aliskiren. At the molecular level, renin-b–deficient mice exhibited increased expression of angiotensin-II type 1 receptor in the paraventricular nucleus, which correlated with an increased renal sympathetic nerve response to leptin, which was dependent on angiotensin-II type 1 receptor activity. Interestingly, despite an ablation of renin-b expression, expression of renin-a was significantly increased in rostral ventrolateral medulla. These data support a new paradigm for the genetic control of RAS activity in the brain by a coordinated regulation of the renin isoforms, with expression of renin-b tonically inhibiting expression of renin-a under baseline conditions. Impairment of this control mechanism causes neurogenic hypertension. Abstract : Supplemental Digital Content is available in the text.